Correlation Between Midwife Knowledge And Attitude, And District Health Service’s Support In The Administration Of Vitamin A Supplementation For Postpartum Women In Working Area Of Puskesmas Seberang Padang And Puskesmas Pemancungan Kota Padang - Dyah Amalia Nauli; Ermawati Ermawati; Yulizawati Yulizawati (Universitas Andalas, 2017)
Current National Guidelines recommends that 100% of postpartum women receive 2 high doses of vitamin A capsules (200.000 IU) within 30 days after giving birth, so the mother can transfer vitamin A to baby through breast milk. Midwife as health worker have big role to achieve this program. This study was aimed to determine correlation of midwife’s knowledge and attitude, and District Health Service’s support in the administration of vitamin A supplementation for postpartum women. This was a qualitative study with cross sectional study design among 32 midwives in working area of Puskesmas Seberang Padang and Puskesmas Pemancungan Kota Padang. The data was obtained using a structured questionnaire. Data were analyzed univariate by using frequency distribution and bivariate using chi square test.Majority of midwife (81,3%) gave vitamin A supplementation to postpartum women, there was a correlation between midwife knowledge with vitamin A administration in postpartum women (p=0,030), there was no correlation between midwife attitude and vitamin A administration in postpartum women (p= 0,063, OR= 7,667, 95% CI= 1,035-56,770) and there was no correlation between district health service’s support with vitamin A administration in the postpartum women (p = 0,029, OR= 11,250, 95% CI= 1,125-112,535).There is a tendency correlation between midwife’s knowledge with vitamin A supplementation to postpartum women, no correlation between midwife’s attitude with vitamin A supplementation to postpartum women and there is a correlation between district health service’s support vitamin A supplementation to postpartum women . The health service is expected to improve the function of supervision and evaluation of midwife's performance